(3fHPI ef GdJYQja hGdCYdGe ajeG CHge aj GdbQBf ef GdCSeGA hGdCYdGes - (3YHO GdQMef Hf YHO Gddg GdNfYej GdSgjdj GdCfOdSj, CHh GdbGSe,J (B581 (3g` s
(3ChdgG (B:s
(3CeG HYO , agPg fHPI eNdUI ef cJGH ef fHi Ch hdi Ch edc Ch Mi Ch HdOI Ch TLQI Ch chcH s
(3BNQgG (B:s
(3hGeQCJg gi Ce Lejd HfJ MQH cGfJ JVY GdThc , hgh GdMWH , Ydi WQjb QShd Gddg Je hHGdNjQ Ye s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG bQGAI SfI (B1064s
(3YdjgG MhGTi cJHJ SfI (B1065(3g` HChdgG JedjcGJ eMOKI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJaSjQ hYdhe GdbQBfs